2017
DOI: 10.1371/journal.pone.0186479
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography angiography vessel density in children with type 1 diabetes

Abstract: PurposeTo assess the optical coherence tomography angiography (OCTA) retinal vessel density and foveal avascular zone (FAZ) in children with type 1 diabetes (T1D) and compare potential pathologic early changes in this population to healthy age-matched controls.MethodsThis study included 130 pubescent children: 94 with T1D (188 eyes) and 36 of their age-matched control group (60 eyes). OCTA was performed using AngioVue (Avanti, Optivue). FAZ area (mm2) in superficial plexus, whole superficial capillary vessel d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
4
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 34 publications
(29 reference statements)
7
51
4
5
Order By: Relevance
“…25 The largest series in type 1 DM have been described in children, and they interestingly have shown controversial results. [26][27][28][29][30] Golebiewska et al reported that no differences were seen in the VD or FAZ area in any of the studied plexuses between patients with type 1 DM and controls (n = 188 vs. 60); however, Niestrata-Ortiz et al described that FAZ area was different between diabetic and healthy children (n = 112 vs. 30). 27,28 In this last paper, a greater FAZ area was also associated with a longer duration of the disease.…”
Section: Discussionmentioning
confidence: 92%
“…25 The largest series in type 1 DM have been described in children, and they interestingly have shown controversial results. [26][27][28][29][30] Golebiewska et al reported that no differences were seen in the VD or FAZ area in any of the studied plexuses between patients with type 1 DM and controls (n = 188 vs. 60); however, Niestrata-Ortiz et al described that FAZ area was different between diabetic and healthy children (n = 112 vs. 30). 27,28 In this last paper, a greater FAZ area was also associated with a longer duration of the disease.…”
Section: Discussionmentioning
confidence: 92%
“…A study on Caucasian children revealed that the size of the FAZ area was 0.240 ± 0.253 mm 2 (Gołębiewska et al. ). Foveal avascular zone (FAZ) was assessed in Caucasian adults by using fluorescein angiography and OCT, and it was found to be 241.0 ± 28.9 in individuals with no‐ and mild diabetic retinopathy (Dmuchowska et al.…”
Section: Discussionmentioning
confidence: 99%
“…Superficial retinal vasculatures (SVs) were imaged in the slab images from the inner boundary 3 μm beneath the internal limiting membrane to the outer boundary 15 μm beneath the IPL, whereas the deep retinal vasculatures (DVs) were imaged in slab images from the inner boundary 15 μm beneath the IPL to the outer boundary 70 μm beneath the IPL, according to the default setting of the manufacturer's software (Optovue, Inc.). 16 , 17 Superficial and deep retinal measurements of the vasculatures were obtained in two regions: (1) macular vessel density was calculated in a 6-mm diameter region and divided into whole macula, superior hemi-macula, and inferior hemi-macula to calculate the hemispheric measurements; (2) parafoveal vessel density was measured in an annular region with an inner diameter of 1 mm and outer diameter of 3 mm centered on the fovea, and the parafoveal region was divided into four sectors (superior, inferior, temporal, and nasal) in addition to superior and inferior hemispheric areas as shown in the Figure .…”
Section: Methodsmentioning
confidence: 99%